2019
DOI: 10.3390/ijms20020452
|View full text |Cite
|
Sign up to set email alerts
|

Isodon rugosus (Wall. ex Benth.) Codd In Vitro Cultures: Establishment, Phytochemical Characterization and In Vitro Antioxidant and Anti-Aging Activities

Abstract: Isodon rugosus (Wall. ex Benth.) Codd accumulates large amounts of phenolics and pentacyclic triterpenes. The present study deals with the in vitro callus induction from stem and leaf explants of I. rugosus under various plant growth regulators (PGRs) for the production of antioxidant and anti-ageing compounds. Among all the tested PGRs, thidiazuron (TDZ) used alone or in conjunction with α-napthalene acetic acid (NAA) induced highest callogenesis in stem-derived explants, as compared to leaf-derived explants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 66 publications
(79 reference statements)
2
41
0
Order By: Relevance
“…No report is present on the production of phenolic compounds in the adventitious root culture of L. usitatissimum until now. However, recently many researchers reported an improvement in the production of phenolics and flavonoids in elicited-cell cultures of L. usitatissimum [13][14][15][16]49], which also endorsed our results. Moreover, many researchers also reported that adventitious root cultures were more potent than callus cultures in the production of phenolic compounds [50].…”
Section: Phenolics Production In Callus and Adventitious Root Culturesupporting
confidence: 90%
See 1 more Smart Citation
“…No report is present on the production of phenolic compounds in the adventitious root culture of L. usitatissimum until now. However, recently many researchers reported an improvement in the production of phenolics and flavonoids in elicited-cell cultures of L. usitatissimum [13][14][15][16]49], which also endorsed our results. Moreover, many researchers also reported that adventitious root cultures were more potent than callus cultures in the production of phenolic compounds [50].…”
Section: Phenolics Production In Callus and Adventitious Root Culturesupporting
confidence: 90%
“…Adventitious roots showed greater antioxidant activity than callus culture, probably due to higher production of phenolics than callus culture. Studies on the antioxidant properties of in vitro cultures of L. usitatissimum are scarce, and only a few reports are available on the antioxidant activity of its callus, hairy root cultures and cell suspension [13][14][15][16]31,32,49]. These investigators reported higher antioxidant activity in hairy root and cell suspension cultures than the callus culture of flax [31].…”
Section: Antioxidant Activity Of Callus and Adventitious Root Culturesmentioning
confidence: 99%
“…Methylation was higher in callus compared with leaves, and the most methylated sequences were CG context and CXG context, whereas CXX sequences essentially lack methylation (Zakrzewski et al 2017). Recent bisulfite sequencing of some maize genome regions (Abbasi et al 2019) revealed that de novo methylation of CG sequence prevailed over methylation of CXG sequence, and the CXX sequence had the lowest methylation levels. Our results showed that de novo methylation was higher than demethylation in the CXX sequence, which is consistent with the results for the control (M10) trial but not for the M13 trial that verified maximum variation.…”
Section: Discussionmentioning
confidence: 99%
“…After extraction, each extract was centrifuged for 15 min at 3,000 rpm and the resulting supernatant filtered using a syringe filter (0.45 µ m, Millipore, Molsheim, France) prior to analysis. The total phenolic content (TPC) was determined spectrophotometrically using the Folin-Ciocalteu reagent (Sigma Aldrich, Saint-Quentin Fallavier, France) and according to the protocol adapted for microplate reader described by Abbasi et al [17]. Briefly, 10 µ L of extract were homogenized with 180 µ L of a mixture composed of 4% Na2CO3 (prepared in NaOH 0.1 M), 0.02% potassium sodium tartrate tetrahydrate and 0.02% CuSO4.…”
Section: Ultrasound-assisted Extraction Methods Developmentmentioning
confidence: 99%